IDENTIFIKASI MISKOSEPSI DALAM PEMBELAJARAN OPTIK POKOK BAHASAN PEMBIASAN PADA MAHASISWA PRODI FISIKA FKIP UNSYIAH - Elisa elisa (JURNAL FISIKA EDUKASI, 2015)
Research entitled "identifying students misconception about refraction in optic courses at physic department of FKIP Unsyiah" explores students’ misconception. The aim of the study is to identify misconception experienced by students of physic department,  FKIP Unsyiah. The subject of the study is all PGMIPAU students in 2014/2015 which is 5 students. The method used is qualitative descriptive. Data collection is undertaken using diagnostic test technique with CRI (Certainty of response Index) and interview. The data is analysed with basic statistic in percentage form. The research found that the average of LG (lucky guess) is 10.6%, TK (tahu konsep) is 74.6%, TTK (tidak tahu konsep) is 9.3%, and M (misconception) is 5.3%. According to the survey, the students experience misconception in understanding the concept of how the image is formed in lens, such as eyes. The result of the study indicates that the average score of students misconception in refraction topic within optic lessons is low which is only 5.3%compared to conceptually students answer. This is due to a good understanding of concept regarding refraction in optic classes. It is suggested to all lectures to analyse students’ early conception so that we can anticipate misconception early as well as deepen students’ understanding about the concept of reflection.